Autokorelasi Spasial Demam Berdarah Dengue di Kota Tasikmalaya: Spatial Autocorrelation of Dengue Haemorrhagic Fever in Tasikmalaya City - Fuadzy, Hubullah; Prasetyowati, Heni; Marliyanih, Elis Siti; Hendra, Asep; Dadang, Abdulah Mubarok (Aspirator, 2021)
Abstract. Tasikmalaya city is a high endemic dengue area which contributes to the high number of dengue cases in West Java province. This study aims to analyze the geographic distribution pattern of dengue infection at the village level and identify high-risk urban villages in Tasikmalaya City. This study analyzed the surveillance data of dengue cases in 2016–2020 which was routinely managed by the Tasikmalaya City Health Office. Variables analyzed included date, patient’s name and address (villages). The map data in the form of a shape file (shp.) were obtained from BPS in 2019. The spatial autocorrelation analysis uses two approaches, (the global Moran Index and LISA). The results showed that DHF cases in the Tasikmalaya city tend to increase in the last 5 years (2016–2020). The highest number of annual and monthly dengue cases occurred in 2020, (1,744 cases and 307 cases) with the incidence rate peaked at 262.6561 per 100,000 population. The global Moran index test using a significance level of 5 showed that there is a spatial autocorrelation between adjacent sub-districts of dengue cases in Tasikmalaya city every year for the last 5 years (2016–2020, and cumulative). The value of the global moran index (I) shows a positive correlation between urban villages to the number of annual dengue cases for the last 5 years and is cumulative. It can be concluded that there are similarities in the characteristics of DHF cases in adjacent villages or the relationship between DHF cases tends to be spatially clustered. Abstrak. Kota Tasikmalaya merupakan daerah endemis tinggi DBD sehingga berkontribusi pula dalam tingginya kasus DBD di Provinsi Jawa Barat. Studi ini bertujuan untuk menganalisa distribusi kasus serta mengidentifikasi wilayah berisiko tinggi kasus DBD berdasarkan tingkat kelurahan di Kota Tasikmalaya. Studi dengan pendekatan deskriptif ini menganalisis data surveilans kasus DBD tahun 2016–2020 yang dikelola secara rutin oleh Dinas Kesehatan Kota Tasikmalaya. Peta tematik Kota Tasikmalaya diperoleh dari Badan Pusat Statistik (BPS) tahun 2019. Analisis data dilakukan secara deskriptif dan autokorelasi spasial dengan pendekatan Indeks Moran global dan Local Indicator of Spatial Autocorrelation (LISA). Hasil analisis menunjukkan kasus DBD di Kota Tasikmalaya cenderung mengalami kenaikan dalam 5 tahun terakhir (2016–2020). Jumlah kasus DBD periode tahunan dan bulanan tertinggi terjadi pada tahun 2020 dan bulan Juli yaitu 1.744 kasus dan 307 kasus. Kelurahan yang masuk dalam peringkat lima besar kasus DBD tinggi dalam 5 tahun terakhir adalah Kahuripan, Sambongpari, Sukamanah. Hasil pengujian autokorelasi spasial (p<0,05) menunjukkan adanya korelasi positif antarkelurahan terhadap jumlah kasus DBD tahunan selama 5 tahun terakhir dan kumulatif dengan pola sebaran mengelompok (Clustering). Kesimpulannya terdapat kemiripan karakteristik kasus DBD antarkelurahan yang berdekatan serta hubungan kasus DBD cenderung berkelompok secara keruangan.